2018
DOI: 10.3390/toxins10020050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Urinary Deoxynivalenol Biomarkers in UK Children and Adolescents

Abstract: Deoxynivalenol (DON), the mycotoxin produced mainly by Fusarium graminearum and found in contaminated cereal-based foodstuff, has been consistently detected in body fluids in adults. Available data in children and adolescents are scarce. This study assessed urinary DON concentrations in children aged 3–9 years (n = 40) and adolescents aged 10–17 years (n = 39) in the UK. Morning urine samples were collected over two consecutive days and analysed for free DON (un-metabolised form), DON-glucuronides (DON-GlcA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
(77 reference statements)
6
26
2
Order By: Relevance
“…For density-adjusted values, a mean daily urine volume of 1500 ml used for adults were used for students in the 8th and 11th school year and 1000 ml for children in the 5th school year. The urinary excretion rate of DON in humans used for the calculation was 72.3% (Turner et al 2010), a value close to that reported in other studies (Ali et al 2016;Faeste et al 2018;Heyndrickx et al 2015;Papageorgiou et al 2018;Warth et al 2012), and for comparative reasons, the same that we have used in previous studies (Mitropoulou et al 2018;Wallin et al 2013). For citrinin, an excretion rate of 40.2% was used (Ali et al 2018).…”
Section: Don Exposure Assessmentsupporting
confidence: 68%
See 2 more Smart Citations
“…For density-adjusted values, a mean daily urine volume of 1500 ml used for adults were used for students in the 8th and 11th school year and 1000 ml for children in the 5th school year. The urinary excretion rate of DON in humans used for the calculation was 72.3% (Turner et al 2010), a value close to that reported in other studies (Ali et al 2016;Faeste et al 2018;Heyndrickx et al 2015;Papageorgiou et al 2018;Warth et al 2012), and for comparative reasons, the same that we have used in previous studies (Mitropoulou et al 2018;Wallin et al 2013). For citrinin, an excretion rate of 40.2% was used (Ali et al 2018).…”
Section: Don Exposure Assessmentsupporting
confidence: 68%
“…The urinary concentration of total DON was generally low among Swedish adolescents (mean of 16.0 ± 21.7 ng/ml, n = 1096), except for a few individuals for which a higher concentration in urine was detected (maximum 102.3 ng/ml). Corresponding figures for adolescents in the UK were 27.0 ng/ml and a maximum at 104.3 ng/ml (Papageorgiou et al 2018). The data from the UK were also published in an EFSA supporting document (Brera et al 2015), which also included data from adolescents in Italy and Norway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also of interest to compare DON biomarker levels in this study to data reported in children from some other countries (Table 4 ) . Exposure to DON in Bangladesh is clearly lower than in two regions of China where 10–73% of the cohorts exceed the TDI (Wang et al 2019 ), or in European cohorts: Belgium with 69% above TDI (Heyndrickx et al 2015 ), Italy with 25–27.5% above TDI (De Santis et al 2019 ), Norway with 20% above TDI (Brera et al 2015 ), and the UK, with 33–63% above the TDI (Papageorgiou et al 2018 ). In Africa, children in Cameroon have apparently lower DON exposure (Ediage et al 2013 ) than those in Tanzania geometric mean 2.5 ng/mL, with 21–54% above TDI in one (Srey et al 2014 ) or more in another study (Gong et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether long-term intake of low concentrations can be prevented and, especially in domestic animals and children, there is concern about the effects of DON including weight loss and reduction of immunity. In a study in Britain, DON was detected in the urine of > 95% of children and adolescents (Papageorgiou et al 2018 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%